Ekstraksi Informasi dari DEM untuk Pemetaan Struktur Geologi Studi Kasus di Daerah Kokap, Kulon Progo - Bayu Raharja; Agung Setianto; Anastasia Dewi Titisari (Universitas Muslim Indonesia, 2020)
Digital elevation model (DEM) data can be used as an input for interpreting geological structures, especially faults. This study aims to determine of extracting geological information from SRTM DEM for geological structure interpretation. Information such as shaded relief, lineament, slope, aspect, drainage network and curvature were used as input for the interpretation using the morphological approach which includes processes, materials, and structures. The vertical exaggeration and sun azimuth and altitude for relief illumination can be varied to obtain different images with different enhanced features. Lineaments can be automatically extracted from the shaded relief. The results showed that the combination of shaded relief, lineament, slope, aspect, drainage network and curvature can be a powerful tool for geological structure interpretation. In general, DEM data analysis can only determine indications of fault location, whereas the types and directions of faults cannot be interpreted.